Spin-anticrossing effects in Co-SiO2-Fe and ZnO-SiO2-CuO three-nanolayer devices - Khmelinskii, Igor (2018)
Presently we report measurements of the spin-anticrossing spectra in the Co-SiO2-Fe and ZnO-SiO2-CuO three-nanolayer sandwich structures. The spin-anticrossing spectra in these systems are quite specific, differing from those observed earlier in other similar structures built of different materials. The theoretical model developed earlier is extended and used to interpret the available experimental results. A detailed ab initio analysis of the magnetic-field dependence of the output magnetic moment is also performed. The model predicts a spin-anticrossing spectrum comprising a series of peaks, with the spectral structure determined by several factors, discussed in the paper. Published by Elsevier Ltd.